99 Privacy Breaches to Beware Of - Shepherdson, Kevin (Marshall Cavendish International (Asia) Private Limited, 2019)
Data protection laws are new in Singapore, Malaysia, Philippines, Indonesia and Thailand. In Europe, the General Data Protection Regulation (GDPR) -- a single law across all of EU - comes into force from May 2018. There are also strict laws in the US that govern the processing of personal data. Over a hundred countries in the world have a comprehensive data protection law and it is very easy for individuals and companies to breach these laws. Data or privacy breaches are on the rise and businesses can be prosecuted under data protection laws. Fines for non-compliance can be from S1 million in.